Branding Strategies Effects in Enhancing SMEs Performance in Saudi Arabia - Al-Tayyar; D. , Raed Saud; Rashid Abdullah, Abdul; Abd Rahman, Azmawani; Hareeza Ali, Mass (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to investigate the relationship of brand experience and brand image to SMEs performance through mediation of brand loyalty. The study is conceptualized in the context of Saudi Arabia. The study highlights the factors that compel customers to show loyalty towards SMEs and the role of loyalty to enhance a firm’s performance. This study includes a theoretical model to describe relationships in a presentable way. In this study, discussion is also being provided to explore relationships further, and limitations of the study are also provided. Future directions also provided for future studies to consider in another services context